Cardiopulmonary transplantation. Issue 10 (October 2018) - Buckland, Mark; Scarr, Bronwyn; Durkin, Chris
Abstract: Heart and lung transplantation rates continue to rise with median survival rates of 11 and 7.4 years, respectively, with transplantation becoming the definitive therapy for end-stage disease of each system. Indications for lung transplantation are categorized as suppurative, obstructive, restrictive and pulmonary vascular. Surgical options include single lung, bilateral sequential single lung and heart–lung transplantation. Each has their own intraoperative challenges, especially at induction, commencement of positive pressure ventilation, one-lung ventilation, pulmonary artery clamping and lung reperfusion. A double lumen tube and a period of one lung ventilation is generally required for cases performed without cardiopulmonary bypass. Strategies to reduce pulmonary pressures and support right ventricular function are important. Perioperative fluids are minimized and lung protective strategies implemented to optimize lung function. Thoracic epidural anaesthesia is commonly used for postoperative pain management. The most common indication for heart transplantation is non-ischaemic cardiomyopathy. Ventricular assist devices and inotropic infusions are often used as a bridge to transplantation. Communication between donor and recipient teams is critical. Reversal of anticoagulation and alteration of implanted medical devices may be necessary. Anaesthetic management requires invasive monitoring, optimization of ventricular function and preparation for coagulopathy. Right ventricular dysfunction is the leading cause of early mortality.